Exploring the physical health of young people with first-episode psychosis - Chee, Gin Liang (Curtin University, 2022)
First-episode psychosis affects young people’s mental and physical capacity to function optimally. In addition, the use of antipsychotic medications to treat psychosis can increase an individual’s risk of developing metabolic syndrome which may lead to serious physical health problems. This research used a mixed methods approach to investigate the impact of psychosis and its treatment on young people’s health and then make recommendations to improve the physical health care for this cohort.